Characterization of Pigments from the Berries of Syzygium caryophyllatum: Novel Source of Anthocyanins - Shetty, Premalatha; Roche, Aveena; Somappa, Sasidhar B (International Journal of Applied Sciences and Biotechnology, 2019)
Extract was prepared from the pulp and peels of the Syzygium caryophyllatum berries. At pH ≤2, the extract showed prominent red coloration and at pH values above 7, the extract attained bluish-green coloration. These typical characteristics indicate presence of anthocyanin pigments in the berries. The yield of the anthocyanins was around 1.9mg per gram wet weight and, around 43% of the anthocyanin pigments appear to be present in polymerized forms.   At pH 1.0, the pigments absorbed maximally at 515nm and at pH 9.0, the pigments were found to absorb to a maximum extent in the range of 380-400nm.  The colors at alkaline pH were unstable, while the red coloration under acidic conditions was relatively stable when exposed to fluorescent light and temperature of 50°C. Mass spectrum of the extract showed predominance of malvidin and petunidine derivatives in the extract. Syzygium caryophyllatum berries can serve as reservoirs of anthocyanin pigments.Int. J. Appl. Sci. Biotechnol. Vol 7(2): 291-297